1992
DOI: 10.1177/019262339202000111
|View full text |Cite
|
Sign up to set email alerts
|

Rat Urinary Bladder Hyperplasia Induced by Oral Administration of Carbonic Anhydrase Inhibitors

Abstract: The carbonic anhydrase inhibitors, acetazolamide and MK-0927, were given by oral route to male SpragueDawley rats at 200 mg/kg/day and 25 mg/kg/day, respectively, for up to 4 weeks. Sequential necropsies were performed and urinary bladders were examined by light microscopy (LM), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Similar urinary bladder changes were seen with both compounds. SEM evidenced slight multifocal urothelial changes consisting of cell swelling, dissociation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Our two hyperplastic urothelial models formed up to nine cell layers and the normoplastic urothelial model formed up to Wve cell layers, which correspond to results in vivo (da Rocha et al 2010;Fukushima et al 1981;Koss and Lavin 1970;Molon-Noblot et al 1992). The functionality of the urothelial barrier in the established hyperplastic and normoplastic urothelial models was investigated by measuring the TER during 2 months of cell culturing.…”
Section: Discussionsupporting
confidence: 77%
“…Our two hyperplastic urothelial models formed up to nine cell layers and the normoplastic urothelial model formed up to Wve cell layers, which correspond to results in vivo (da Rocha et al 2010;Fukushima et al 1981;Koss and Lavin 1970;Molon-Noblot et al 1992). The functionality of the urothelial barrier in the established hyperplastic and normoplastic urothelial models was investigated by measuring the TER during 2 months of cell culturing.…”
Section: Discussionsupporting
confidence: 77%
“…No evidence of dysplasia, aplasia, or any change that would suggest tumor formation was apparent. Urinary formation of microcalculi (consistent with carbonic anhydrase inhibition) was seen in studies of rats and mice (30). In teratology studies, TPM caused right-sided ectrodactyly (congenital absence of all or part of a digit) in rats, and rib and vertebral malformations in rabbits (1) similar to those reported with acetazolamide and other carbonic anhydrase inhibitors (31)(32)(33).…”
Section: Toxicitymentioning
confidence: 62%
“…454À456 A review of the bladder mucosa of laboratory cynomolgus monkeys showed that the urothelium and submucosa may normally contain multifocal or diffuse infiltrate of lymphocytes and macrophages of variable intensity. 461,462 A detailed study of the effects of carbonic anhydrase inhibitors in the rat showed that inflammation developed shortly after the first dose but diminished after longer periods of dosing to be replaced by hyperplasia of the urothelium. A notable example is the anticancer drug cyclophosphamide, which is activated by hepatic microsomal enzymes to potent alkylating cytotoxic metabolites.…”
Section: Inflammation Cystitismentioning
confidence: 99%